Axisymmetric adaptive upper-bound finite element limit analysis formulation based on second-order cone programming for bearing capacity of circular footing - Rui Sun; Haibing Cai; Kai Zhang (PLoS ONE, 2025)
An adaptive axisymmetric upper bound finite element limit analysis (UB-FELA) formulation has been presented for Mohr-Coulomb (M-C) materials in this paper. The computational domain is discretized using quadratic velocity elements. For the sake of computational efficiency, the axisymmetric UB finite element problem is recast into a model of second-order cone programming (SOCP). To enhance the precision of the proposed UB finite element method using a reduced element count, this study implements a mesh adaptation algorithm grounded in plastic dissipation. The collapse loads for determining the circular footings are then estimated by application of the proposed axisymmetric UB limit analysis formulas. By comparing the results to those reported in the literature, the analysis indicates that the method presented in this paper yields an accurate UB solution.